Ultra low-power negative DC voltage generator based on a proposed level shifter and voltage reference. (July 2021) - Rezaei, Neda; Mirhassani, Mitra
Abstract: With advances in low power and battery-operated devices, concerns over power-efficient designs for system-on-chip devices is growing. Since some subsystems require to have both positive and negative voltage rails, it is essential to ensure this requirement is satisfied without increasing the cost and power consumption. This paper presents a novel Negative Level Shifter used to generate negative voltage levels from the positive DC power supply line. Additionally, an improved CMOS Voltage Reference generator based on a Resistorless Beta Multiplier is also proposed. The two circuits were tested under various conditions, and results validate the low-power operation of the proposed design. The proposed Negative Level Shifter required only 772 pW and has a delay equal to 4ns with a supply voltage of 0.3 V . When assembled, both the reference voltage and the level shifter consume 8.5 nW with the supply voltage of 1 V at room temperature.